2010
DOI: 10.1088/1742-5468/2010/11/p11001
|View full text |Cite
|
Sign up to set email alerts
|

True nature of long-range order in a plaquette orbital model

Abstract: We analyze the classical version of a plaquette orbital model that was recently introduced and studied numerically by S. Wenzel and W. Janke. In this model, edges of the square lattice are partitioned into x and z-types that alternate along both coordinate directions and thus arrange into a checkerboard pattern of x and z-plaquettes; classical O(2)-spins are then coupled ferromagnetically via their first components over the x-edges and via their second components over the z-edges. We prove from first principle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The 90 • compass, where both ferro-and anti-ferromagnetic coupling appear across the two orthogonal diagonals here, has been proposed as a model to Mott insulators with orbital degrees of freedom and frustrated magnets [29]. Other compass-type models accessible through polariton graphs include the plaquette orbital model, where the ferromagnetic and anti-ferromagnetic coupling alternate along each direction [30] and the orbital compass model on a checkerboard lattice [31]. Fully random couplings in the square lattice describes the thermodynamic behaviour of several disordered systems, such as magnetic systems with random Dzyaloshinskii-Moriya interactions [32], disordered Josephson junction arrays [33], disordered substrates [34], and vortex glasses in high-T c cuprate superconductors [35].…”
mentioning
confidence: 99%
“…The 90 • compass, where both ferro-and anti-ferromagnetic coupling appear across the two orthogonal diagonals here, has been proposed as a model to Mott insulators with orbital degrees of freedom and frustrated magnets [29]. Other compass-type models accessible through polariton graphs include the plaquette orbital model, where the ferromagnetic and anti-ferromagnetic coupling alternate along each direction [30] and the orbital compass model on a checkerboard lattice [31]. Fully random couplings in the square lattice describes the thermodynamic behaviour of several disordered systems, such as magnetic systems with random Dzyaloshinskii-Moriya interactions [32], disordered Josephson junction arrays [33], disordered substrates [34], and vortex glasses in high-T c cuprate superconductors [35].…”
mentioning
confidence: 99%
“…We have shown that the local average values of these effective spins correspond with the average values of the bonds in the initial ladder so the long-range spin-spin correlations in the ground-subspace are the long-range bond-bond correlations in the Cx-Cz model. This resembles the Néel order of the plaquettes energies found in the two-dimensional plaquette orbital model [40], however it has been shown that this is an artifact of a deeper lying orientational order [41]. The polarized ground state configuration of the effective spins is slightly distorted by the quantum interaction terms that cause a two-sublattice modulation of the order such that the sublattices are related by the interchange of the x and z spin components.…”
Section: Discussionmentioning
confidence: 60%
“…The interest in the 2D compass model is motivated by new opportunities it provides for quantum computing [26]. This motivated also plaquette orbital model (POM) introduced for a square lattice by Wenzel and Janke [40] which exhibits orientational long-range order in its classical version [41]. Here we will focus on the 1D quantum version of the POM and investigate the nature of the ground state and of low energy excitations.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear, though, whether this might lead to useful results for the study of this specific model. Another relevant model is the plaquette orbital model that was studied in [28,3]; interactions between neighbours x, y are of the form −S i x S i y , with i being equal to 1 or 3 depending on the edge.…”
Section: Setting and Resultsmentioning
confidence: 99%